2023
DOI: 10.1523/jneurosci.1745-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Development of Human Lateral Prefrontal Sulcal Morphology and Its Relation to Reasoning Performance

Abstract: Previous findings show that the morphology of folds (sulci) of the human cerebral cortex flatten during postnatal development. However, previous studies did not consider the relationship between sulcal morphology and cognitive development in individual participants. Here, we fill this gap in knowledge by leveraging cross-sectional morphological neuroimaging data in the lateral prefrontal cortex (LPFC) from individual human participants (6-36 years old, males and females; N = 108; 3672 sulci), as well as longit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 101 publications
3
52
0
Order By: Relevance
“…Indeed, the presence/absence and morphology of sulci are theorized to be anatomically linked to cortical white matter development (Sanides 1962, 1964; Van Essen et al 2014; Reveley et al 2015; Van Essen 2020; Cottaar et al 2021; Miller et al 2021b; Cachia et al 2021), and the presence of sulci relates to changes in the local cytoarchitectonic organization of gray matter (Amiez et al 2021). Neural efficiency is the foundation of our hypothesis regarding relationships between sulcal anatomy and reasoning observed in these and other studies (Voorhies et al 2021; Willbrand et al 2023b). Specifically, we (and others; Garrison et al, 2015) hypothesize that these sulcal-behavioral relationships stem from individual differences in white matter projections and, in turn, the distributed functional brain networks that underlie higher-level cognition.…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, the presence/absence and morphology of sulci are theorized to be anatomically linked to cortical white matter development (Sanides 1962, 1964; Van Essen et al 2014; Reveley et al 2015; Van Essen 2020; Cottaar et al 2021; Miller et al 2021b; Cachia et al 2021), and the presence of sulci relates to changes in the local cytoarchitectonic organization of gray matter (Amiez et al 2021). Neural efficiency is the foundation of our hypothesis regarding relationships between sulcal anatomy and reasoning observed in these and other studies (Voorhies et al 2021; Willbrand et al 2023b). Specifically, we (and others; Garrison et al, 2015) hypothesize that these sulcal-behavioral relationships stem from individual differences in white matter projections and, in turn, the distributed functional brain networks that underlie higher-level cognition.…”
Section: Discussionmentioning
confidence: 71%
“…Continuous Measurements: Building upon our prior work (11,12,13), to analyze continuous morphological sulcal-behavior relationships, we leveraged a pre-existing pipeline that tests for a relationship between sulcal morphology (i.e., sulcal depth) and ERI via the following approach:…”
Section: Discussionmentioning
confidence: 99%
“…We then implemented a model-based LASSO regression to relate OFC sulcal morphology to ERI, and subsequently tested whether effects were specific to ERI as compared to non-emotion-related impulsivity. We focused on sulcal depth as it is one of the main morphological features differentiating putative primary (deepest), secondary, and tertiary (shallowest) sulci from one another and recent research identifies a link between sulcal depth and cognition (11)(12)(13)(14). To our knowledge, this is the first study to examine the relationship between ERI and sulci identified in each individual hemisphere (including putative tertiary sulci, which have been largely overlooked and are considerably variable across hemispheres (15,(18)(19)), which is consistent with what has been referred to recently as a "precision imaging" approach (20).…”
Section: Introductionmentioning
confidence: 99%
“…(a) Left hemisphere FreeSurfer inflated cortical reconstruction (gyri: light gray, sulci: dark gray) from an example Human Connectome Project participant (neuroimaging data from https://db.human conne ctome.org/) focused on the lateral prefrontal cortex (LPFC; inset for the location of the zoomed portion). LPFC sulci have been manually defined (outlined) based on the most recent atlas (Petrides, 2019) and published previously in this individual (Miller et al, 2021;Willbrand et al, 2023). Red sulci are those excluded from the present tool, whereas blue sulci are those included.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%